Transcatheter mitral valve replacement: tissue in-growth after 4 weeks. (6th December 2020) - Lutter, Georg; Bax, Lennart; Liu, Yazhou; Hansen, Jan-Hinnerk; Frank, Derk; Freitag-Wolf, Sandra; Simionescu, Agneta; Sathananthan, Janarthanan; Puehler, Thomas
Abstract: OBJECTIVES: Tissue reaction to transcatheter mitral valve replacement in the mitral annulus remains to be elucidated. METHODS: Trileaflet porcine pericardial valves were sewn onto self-expanding d-shaped nitinol stents, which were delivered transapically and in an off-pump fashion into the mitral position of 10 pigs. After at least 4 weeks of follow-up, gross pathological assessment and histological examination were performed. The specimens were stained with Movat's pentachrome, Elastica-van-Gieson and von Kossa staining. The leucocytes, B cells, T cells or macrophages were detected by specific immunohistochemical staining. RESULTS: Proper stent positioning in the mitral annulus was achieved in 9/10 animals. Nine of 10 animals survived the desired observation period. In all but one, the mitral valve stent was well integrated into the left atrium and perpendicularly embedded into the annulus by 85 ± 24%. One animal had minor fractures in the nitinol struts and another animal showed tearing of 1 of 4 tethers. Histological examination demonstrated no major tissue reaction with the nitninol struts but well-preserved overall structures around the mitral annulus in 8/9 cases. CONCLUSIONS: This is the first report demonstrating good in-growth of transcatheter-delivered anatomically shaped mitral valve stents after at least 4 weeks of follow-up. Histological examination demonstrated progressive healing and neointimalization.